Effects of Temperature and Nitrogen Application on Carbon and Nitrogen Accumulation and Bacterial Community Composition in Apple Rhizosphere Soil - Zhang, Huanhuan; Phillip, Fesobi Olumide; Wu, Linnan; Zhao, Fengyun; Yu, Songlin; Yu, Kun (Frontiers in Plant Science, 2022)
Malus sieversii grows on the slopes of the Tianshan Mountains in Xinjiang where the difference in daily temperature is significant. In recent years, the rhizosphere soil health of Malus sieversii has been severely impacted by anthropogenic disturbance and pathogenic infestation. The soil nutrient content and soil microorganism diversity are the main components of soil health. Low temperature has negative effects on soil bacterial community structure by inhibiting the accumulation of carbon and nitrogen. However, the effects of temperature and nitrogen application on soil carbon and nitrogen accumulation and the bacterial community composition in the rhizosphere soil of Malus sieversii are unclear. We set two temperature levels, i.e., low temperature (L) and room temperature (R), combined with no nitrogen (N0) and nitrogen application (N1) to explore the response of plant carbon and nitrogen uptake, rhizosphere soil carbon and nitrogen accumulation and bacterial community composition to temperature and nitrogen fertilization. At the same temperature level, plant 13C abundance (P-Atom13C), plant 15N absolute abundance (P-Con15N), soil 15N abundance (S-Atom15N) and soil urease, protease and glutaminase activities were significantly higher under nitrogen application compared with the no-nitrogen application treatment. The bacterial community diversity and richness indices of the apple rhizosphere soil in the N1 treatment were higher than those in the N0 treatment. The relative abundances of Actinobacteria, Rhodopseudomonas and Bradyrhizobium were higher in the LN1 treatment than in the LN0 treatment. Redundancy analysis (RDA) showed that plant 13C absolute abundance (P-Con13C) and plant 15N absolute abundance (P-Con15N) were the main factors affecting the soil bacterial community composition. In summary, Nitrogen application can alleviate the effects of low temperature stress on the soil bacterial community and is of benefit for the uptakes of carbon and nitrogen in Malus sieversii plants.